Interactive Multimedia in Physical Education: The Effectiveness of Powtoon in Improving Learning Outcomes in Elementary Schools - Oman; Shofiatul Khusnah; Arita Marini; Gusti Yarmi; Desy Safitri; Sujarwo; Musril Zahari; Leola Dewiyani (Jurnal Edutech Undiksha, 2024)
The low learning outcomes in physical education among elementary school students are attributed to the use of less interactive and engaging learning media. This condition hinders students' engagement in the learning process, necessitating media innovation to enhance their interest and comprehension. This study aims to develop Powtoon-based interactive multimedia to improve the learning outcomes of fourth-grade elementary school students in physical education. The research employed a research and development (R&D) method by adapting a development model encompassing needs analysis, design, development, and product evaluation stages. Data were collected through pretest and post-test learning outcome assessments conducted before and after the use of interactive media. Data analysis included normality tests using the Kolmogorov-Smirnov test and homogeneity tests using SPSS version 24, indicating that the data were normally distributed and homogeneous. The t-test results demonstrated a significant difference between pretest and post-test learning outcomes, showing that students' learning outcomes improved significantly after using Powtoon-based interactive multimedia. These findings indicate that Powtoon-based interactive multimedia is effective in enhancing physical education learning outcomes. Therefore, it can be concluded that the use of Powtoon-based interactive multimedia has a positive impact on improving the physical education learning outcomes of fourth-grade elementary school students.